Proteasomal degradation from internal sites favors partial proteolysis via remote domain stabilization - Kraut, Daniel A. (2011)
The ubiquitin-proteasome system controls the concentrations of hundreds of regulatory proteins and removes misfolded and damaged proteins in eukaryotic cells. The proteasome recognizes ubiquitinated proteins and then engages its substrates at unstructured initiation regions. After initiation, it proceeds along the polypeptide chain, unraveling folded domains sequentially and degrading the protein completely. In vivo the proteasome can, and likely often does, initiate degradation at internal sites within its substrates but it is not known how this affects the outcome of the degradation reaction. Here we find that domains flanking the initiation region can protect each other against degradation without interacting directly. The magnitude of this effect is related to the stability of both domains and can be tuned from complete degradation to complete protection of one domain. Partial proteasomal degradation has been observed in the cell in three signaling pathways and is associated with internal initiation. Thus, the basic biochemical mechanism of remote stabilization of protein domains is important in proteasome biology.